Apremilast in paediatric dermatoses – A comprehensive review - Nibedita Patro; Maitreyee Panda; Mrityunjay Dash; Anupam Das (Indian Journal of Dermatology, 2022)
Apremilast has recently garnered attention in the management of multiple dermatological conditions including psoriasis. The comparable effectiveness with immunosuppressive drugs and a favorable side effect profile makes the drug, a prudent alternative for managing a gamut of dermatoses. In this article, we have reviewed the literature on apremilast use in children.